Türkiye Ulusal Yatay Kontrol Ağı’nın Kuzeybatı Bölümünde Yer Kabuğu Hareketleri Nedeniyle Oluşan Deformasyonun Yersel Ve Gps Ölçüleri İle Araştırılması - Açıkgöz, Mehmet (Fen Bilimleri Enstitüsü, 2010)
Bu çalışmada, Türkiye Ulusal Yatay Kontrol Ağı’nın kurulması ve sıklaştırılması kapsamında yapılan yersel ölçüler ile daha sonraki yıllarda yapılan GPS ölçüleri birlikte değerlendirilerek Yatay Kontrol Ağı’nın kuzeybatı bölümünde yer kabuğu hareketleri sonucu oluşan deformasyon araştırılmıştır. Bölgedeki ağ noktalarında oluşan deformasyonun ortaya çıkarılmasında; bölgede 1930–2003 yılları arasında meydana gelen ve jeodezik ağları etkilediği değerlendirilen (M≥6) depremler, Yatay Kontrol Ağı’nda 1930-1964 yıllarında yapılan yersel ölçüler ve bu ağın 82 noktasında 2000 ve 2003 yıllarında yapılan GPS ölçüleri kullanılmıştır. Ağdaki deformasyonun belirlenmesinde, öncelikle 1930-1964 yılları arasında meydana gelen 06 Ekim 1944 Ayvalık (Ms=6.8), 18 Mart 1953 Gönen (Ms=7.2) ve 06 Ekim 1964 Manyas (Ms=6.9) depremleri göz önüne alınarak yersel ölçüler 01.01.1930-06.10.1944, 01.01.1930-18.03.1953 ve 19.03.1953-05.10.1964 olmak üzere üç evreye ayrılmıştır. Daha sonra, üç evre yersel ölçünün GRS80 elipsoidinde ITRF koordinat sisteminde dengelenmesi ve sonuçların güncel GPS koordinatları ile karşılaştırılması ile ağ noktalarında oluşan yer değiştirmeler hesaplanmıştır. Buna göre; Yatay Kontrol Ağı’nın bu bölgedeki noktalarında yaklaşık 50 yıllık zaman içinde tektonik hareketler (deprem öncesi, deprem anı ve deprem sonrası) sonucu oluşan toplam yatay yer değiştirmenin 3.5 m’ye ulaştığı belirlenmiştir. Ayrıca, bölgede sadece depremler nedeniyle ağ noktalarında oluşan kosismik ve postsismik deformasyonun 2-3 m civarında olduğu değerlendirilmektedir. Yatay Kontrol Ağı’ndaki bu deformasyon, ülkemizin teknik ve hukukî altyapısının kurulu olduğu ED-50 datumu ile TUTGA arasındaki dönüşümünün sadece geometrik olmadığını ve tektonik hareketler gibi fiziksel etkilerin de bu dönüşümün içinde önemli rolünün olduğunu göstermektedir.

In this study, deformation in the northwest part of the Turkish National Horizontal Control Network due to crustal movements is investigated by using both terrestrial measurements, which were made during the establishment and densification phases of the horizontal control network, and GPS measurements of the late years. In order to determine the deformation at the sites in the region, the data used are as of the followings: the earthquakes which are considered to be strong enough in magnitude to affect the geodetic network ( ) between 1930 and 2003, terrestrial measurements at the Horizontal Control Network between 1930 and 1964 and GPS measurements performed at the 82 common sites of the network in the years 2000 and 2003. During the determination of deformation at the network, the terrestrial measurements between 1930 and 1964 were primarily grouped into three phases as of 01.01.1930-06.10.1944, 07.10.1944-18.03.1953 and 19.03.1953-05.10.1964 by taking account of the 06 October 1944 Ayvalık (Ms=6.8), 18 March 1953 Gönen (Ms=7.2) and 06 October 1964 Manyas (Ms=6.9) earthquakes. Then, the displacements in the network were determined by comparing the up-to-date GPS coordinates with the ones which were derived from the adjustment of terrestrial observations between 1930 and 1964 in ITRF reference frame together with the GRS80 ellipsoid. Thus, total horizontal displacement is found to have reached about 3.5 m at some of the points in the network due to tectonic activities (interseismic, coseismic and postseismic) in the last 50 years. What is more, the coseismic and postseismic deformation at the triangulation sites caused by the earthquakes is believed to be about 2 or 3 metres in the region. The deformation at the triangulation points depicts that the datum transformation between ED50 which the has the technical and legal infrastructure of the country and TNFGN is not purely geometrical. It is also seen that the physcal effetcs such as tectonic (interseismic, coseismic and postseismic) movements have an important role in the transformation.
Investigation Of Deformation In The Northwest Part Of Turkish National Horizontal Control Network Due To Crustal Movements Using Terrestrial And Gps Data
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2010
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2010
Keywords: Deformasyon; triyangulasyon; GPS; deprem; Deformation; triangulation; GPS; earthquake